Solving the multi-objective flexible job shop scheduling problem with a novel parallel branch and bound algorithm - Soto, Carlos; Dorronsoro, Bernabé; Fraire, Héctor; Cruz-Reyes, Laura; Gomez-Santillan, Claudia; Rangel, Nelson (Swarm and evolutionary computation, 2020)
This work presents a novel parallel branch and bound algorithm to efficiently solve to optimality a set of instances of the multi-objective flexible job shop scheduling problem for the first time, to the very best of our knowledge. It makes use of the well-known NSGA-II algorithm to initialize its upper bound. The algorithm is implemented for shared-memory architectures, and among its main features, it incorporates a grid representation of the solution space, and a concurrent priority queue to store and dispatch the pending sub-problems to be solved. We report the optimal Pareto front of thirteen well-known instances from the literature, which were unknown before. They will be very useful for the scientific community to provide more accuracy in the performance measurement of their algorithms. Indeed, we carefully analyze the performance of NSGA-II on these instances, comparing the results against the optimal ones computed in this work. Extensive computational experiments show that the proposed algorithm using 24 cores achieves a speedup of 15.64x with an efficiency of 65.20%. •Parallel Branch-and-Bound for Multi-objective Flexible Job Shop Scheduling Problem.•A new permutation-based representation for FJSSP for reduced search complexity.•Novel upper bound based on a grid representation of the Pareto frontier.•Integration of a priority queue to first explore the most promising sub-problems.•Generalized Integer Vector Matrix for integer representations.